Implementasi Metode Fuzzy Time Series Cheng untuk prediksi Kosentrasi Gas NO2 Di Udara - Fathoni, M Yoka (Universitas Diponegoro, 2017)
The forecasting process is essential for determining air quality to monitor NO2 gas in the air. The research aims to develop prediction information system of NO2 gas in air. The method used is Fuzzy Time Series Cheng method. The process of acquiring NO2 gas data is integrated with Multichannel-Multistasion. The data acquisition process uses Wireless Sensor Network technology via broadband internet that is sent and stored in an online database form on the web server. Recorded data is used as material for prediction. Acquisition result ofÂ NO2 gas data is obtained from the sensor which is sent to the web server in the data base in the network by on line, then for futher it is predicted using fuzzy time series Cheng applying re-divide to the results of intervals the first partition of the value of the universe of discourse by historical data fuzzification to determine Fuzzy Logical Relationship dan Fuzzy Logical Relationship Group, so that is obtained result value prediction of NO2 gas concentration. By using 36 sample data of NO2 gas, it is obtained that the value of root of mean squared error of 2.08%. This result indicates that the method of Fuzzy Time Series Cheng is good enough to be used in predicting the NO2 gas.